Severe Acute Respiratory Syndrome Coronavirus-2 Infection and Autoimmunity 1 Year Later: The Era of Vaccines - Picchianti Diamanti, Andrea; Rosado, Maria Manuela; Nicastri, Emanuele; Sesti, Giorgio; Pioli, Claudio; Laganà, Bruno (Frontiers in Immunology, 2021)
Impressive efforts have been made by researchers worldwide in the development of target vaccines against the novel Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) and in improving the management of immunomodulating agents. Currently, different vaccine formulation, such as viral vector, mRNA and protein-based, almost all directed toward the spike protein that includes the domain for receptor binding, have been approved. Although data are not conclusive, patients affected by autoimmune rheumatic diseases (ARD), seem to have a slightly higher disease prevalence, risk of hospitalization and death from COronaVIrus Disease-2019 (COVID-19) than the general population. Therefore, ARD patients, under immunosuppressive agents, have been included among the priority target groups for vaccine administration. However, specific cautions are needed to optimize vaccine safety, and effectiveness in these patients, such as modification in some of the ongoing immunosuppressive therapies and the preferential use of mRNA other than vector-based vaccines. Immunomodulating agents can be a therapeutic opportunity for the management of COVID-19 patients, however their clinical impact depends on how they are handled. To place in therapy immunomodulating agents in the correct window of opportunity throughout the identification of surrogate markers of disease progression and host immune response, is mandatory to optimize patient’s outcome.